2021
DOI: 10.2147/vhrm.s205130
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Patient Following Radio-Cephalic Arteriovenous Fistula Creation: Current Perspectives

Abstract: Autogenous radial-cephalic direct wrist arteriovenous fistula (RC-AVF) in the non-dominant arm is the gold standard for dialysis vascular access. However, the RC-AVF non-maturation rate is significant (≃ 40%) due to an increasingly elderly and comorbid population incidence. A detailed identification of the biological cascade underlying arteriovenous fistula (AVF) maturation could be the key to clinical research aimed at identify the group of patients at risk of primary AVF failure. Currently, careful post-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 73 publications
0
13
0
1
Order By: Relevance
“…In general, AVF represents the best vascular access in HD and should be the first choice according to different guidelines [ 20 , 37 , 38 ], due to a better function with lower complications and mortality. It is well known that determining the optimal vascular access is based on a multitude of factors such as age, gender, comorbidities, life expectancy, patient anatomy, surgeon experience and organizing capacities of the single HD center [ 39 , 40 ]. The concerns about smaller vessels in women, leading to poorer AVF maturation and less long-term patency, may have prevented nephrologists and surgeons from considering AVF in female HD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, AVF represents the best vascular access in HD and should be the first choice according to different guidelines [ 20 , 37 , 38 ], due to a better function with lower complications and mortality. It is well known that determining the optimal vascular access is based on a multitude of factors such as age, gender, comorbidities, life expectancy, patient anatomy, surgeon experience and organizing capacities of the single HD center [ 39 , 40 ]. The concerns about smaller vessels in women, leading to poorer AVF maturation and less long-term patency, may have prevented nephrologists and surgeons from considering AVF in female HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The concerns about smaller vessels in women, leading to poorer AVF maturation and less long-term patency, may have prevented nephrologists and surgeons from considering AVF in female HD patients. Several studies have showed no differences in vasculature of females in HD by duplex ultrasound examination, with consequent adequacy of AVF placing [ 21 , 40 ]. Even if it seems that vein and arterial anatomy and caliber do not differ significantly by gender, some authors have hypothesized that the worst AVF outcome reported in women in some studies [ 21 , 41 ], but not in others [ 42 ], may persuade surgeons and nephrologists to prefer CVC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the commonly used artificial arterio-venous fistulas and the rarely applicable loop-shaped grafts (arterial or venous interposition), failure is still a challenging problem [ 2 , 7 , 8 ]. Arterio-venous interposition grafts can be used in clinical reconstructive microsurgery when proper vessels are not available or long enough in free flap operations [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Physical examination (PE) has a reasonable efficacy for identifying complications in fistulas. Physical assessment is handily educated, effortlessly performed, ---------------------------------------------------------------------------------------Received on 21-08-2021 Accepted on 11-01-2022 immediately done, and cost-effective 8 . Doppler ultrasound is a straightforward, economical, and harmless strategy for the evaluation of blood flow in AVF.…”
Section: Introductionmentioning
confidence: 99%